A question of standards: Adapting carbon and other PES markets to work for community seagrass conservation. (July 2021) - Shilland, Robyn; Grimsditch, Gabriel; Ahmed, Mohamed; Bandeira, Salomão; Kennedy, Hilary; Potouroglou, Maria; Huxham, Mark
Abstract: Seagrass meadows deliver multiple ecosystem services that are of particular importance to resource-poor coastal communities, yet they are rapidly declining globally. The Payments for Ecosystem Services (PES) approach has been used to fund the protection of other 'Blue Carbon' Ecosystems (BCE), yet seagrass has been incorporated in just one PES project worldwide. Some of the ecosystem services delivered by seagrass have the potential for inclusion under a PES framework but multiple challenges currently make this difficult, particularly under community-based management. PES programmes typically focus on carbon as the tradable service, but scientific uncertainties regarding seagrass carbon are likely to remain significant barriers to using carbon as the sole commodity under current carbon trading standards and market conditions. It is recommended here that project developers demonstrate the multiple ecosystem services delivered by seagrass meadows, along with their importance to coastal communities, in the planning and marketing of seagrass PES projects. Moreover, they should consider approaches that incorporate seagrass meadows into other blue carbon certified projects. The capacities of the communities that rely most heavily on seagrass are generally very limited. Consequently, demanding high levels of scientific certainty over carbon stocks and flows will exclude most of these communities. Standards, buyers and policy makers should consider building community capacity in the technical and marketing requirements of voluntary carbon standards. The voluntary carbon market has the flexibility to pioneer certified seagrass carbon, potentially leading to the inclusion of seagrass carbon in formal policy instruments, such as Nationally Determined Contributions (NDCs). Highlights: Seagrass meadows deliver a plethora of ecosystem services but protection is lacking. There has been limited inclusion of seagrass under certified carbon trading projects. The voluntary carbon market can facilitate innovation and experimentation in CBM. Multiple ecosystem services should be considered under certification of seagrass. CBM of seagrass can contribute to climate, biodiversity and development targets.